INFLUENCE OF THE PROBIOTIC DRUG ON THE MICROBIOCENOSIS OF THE UPPER RESPIRATORY TRACT IN PATIENTS WITH THE ACUTE MYELOID LEUKEMIA - Melnyk, O.A.; Rybalska, A.P.; Goryainova, N.V.; Tretyak, N.N. (World of Medicine and Biology, 2019)
In 22 patients with acute myeloid leukemia in the stages of induction and consolidation of remission in the dynamics of probiotics therapy, microbiological monitoring of the upper respiratory tract microbiota was performed. The 186 strains of bacteria, yeast and mycelial funguses were isolation. After the end of probiotic intake, in the patients observed elimination from the biotopes of upper respiratory tract opportunistic microorganisms such as Corynebacterium, Enterococcus, Aspergillus, S.aureus, S.epidermidis, S.saprophyticus. "Hidden pathogens" - microorganisms that were not isolated at the beginning of the study - S.epidermidis and S.aureus, Moraxella catarrhalis, Micrococccus, Enterococcus, Actinomyces, Aspergillus and Candida were detected in 10 (46%) patients after the course of probiotics. Established phenomenon of "hidden pathogens" allows us comprehensively to characterize the microbiocenosis of patients and obtain an additional diagnostic effect in terms of determining the etiological factors.